Designing Android-Based Learning Media for Student Engagement Using the ISpring-Suite 10 Application - Yeni, Yeni; Suardika, I Ketut; Ningsih, Sindi Subhi Cahya (Proceeding International Conference on Religion, Science and Education, 2025)
This study aims to apply Android-based learning media to high school students in grade XI using the spring application. The method used in this study uses the ADDIE method, which aims to create, develop, and produce a product. The results obtained from this study indicate that this Android application-based learning media is designed using Canva, Microsoft PowerPoint, Ispring Suite 10, and Website 2 APK builder, which are presented in several menus on the main menu page, namely learning objectives, learning materials, and evaluations. The learning objectives menu has several objectives for students studying the mechanical wave material. In the learning material menu, there are 3 choices of material presented for students to research and accompanied by animation. In the evaluation menu, there are 5 multiple-choice questions. The application of learning media on the mechanical wave material based on Android can help students, especially grade XI students, understand the material and make it easier for students to learn anywhere and anytime without having to bring books and not requiring an internet connection.